2016
DOI: 10.1016/j.bmcl.2016.04.090
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic potentiation of (−)-lomaiviticin A cytotoxicity by the ATR inhibitor VE-821

Abstract: (−)-Lomaiviticin A (1) is a cytotoxic bacterial metabolite that induces double-strand breaks in DNA. Here we show that the cytotoxicity of (−)-lomaiviticin A (1) is synergistically potentiated in the presence of VE-821 (7), an inhibitor of ataxia telangiectasia and Rad3-related protein (ATR). While 0.5 nM 1 or 10 μM 7 alone are non-lethal to K562 cells, co-incubation of the two leads to high levels of cell kill (81% and 94% after 24 and 48 h, respectively). Mechanistic data indicate that cells treated with 1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…We also found that the ataxia telangiectasia and Rad3-related protein (ATR) inhibitor VE-821 53 synergizes with (−)-lomaiviticin A (4). 54 Exposure of K562 cells to either 10 μM VE-821 or 500 pM (−)-lomaiviticin A (4) alone for up to 48 h was nonlethal. However, when treated with 10 μM VE-821 + 500 pM (−)-lomaiviticin A (4), the cells suffered 81% and 94% killing after 24 and 48 h, respectively.…”
Section: Translational Development Of (−)-Lomaiviticin a (4)mentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that the ataxia telangiectasia and Rad3-related protein (ATR) inhibitor VE-821 53 synergizes with (−)-lomaiviticin A (4). 54 Exposure of K562 cells to either 10 μM VE-821 or 500 pM (−)-lomaiviticin A (4) alone for up to 48 h was nonlethal. However, when treated with 10 μM VE-821 + 500 pM (−)-lomaiviticin A (4), the cells suffered 81% and 94% killing after 24 and 48 h, respectively.…”
Section: Translational Development Of (−)-Lomaiviticin a (4)mentioning
confidence: 99%
“…Sensitivity to (−)-lomaiviticin ( 4 ) conferred by deficiencies in ATM- and X-ray repair cross complementing 5 (KU80) are also consistent with the involvement of DNA damage and DSB formation. We also found that the ataxia telangiectasia and Rad3-related protein (ATR) inhibitor VE-821 synergizes with (−)-lomaiviticin A ( 4 ) . Exposure of K562 cells to either 10 μM VE-821 or 500 pM (−)-lomaiviticin A ( 4 ) alone for up to 48 h was nonlethal.…”
Section: The Dimeric Diazofluorene Is Required For Potent Cytotoxicitymentioning
confidence: 99%
“…The C 2 -symmetric bacterial metabolite (−)-lomaiviticin A ( 1 , Scheme 1) induces double-strand breaks (DSBs) in DNA 1 and is undergoing preclinical evaluation as a combination 2 and monotherapy 1e for the treatment of DNA DSB repair-deficient tumors. 3 1 binds DNA by a mode of association involving penetration of both diazotetrahydrobenzo[ b ]fluorene (diazofluorene) residues into the duplex.…”
mentioning
confidence: 99%
“…The C 2 -symmetric bacterial metabolite (–)-lomaiviticin A ( 1 , Scheme ) induces double-strand breaks (DSBs) in DNA and is undergoing preclinical evaluation as a combination and monotherapy for the treatment of DNA DSB repair-deficient tumors .…”
mentioning
confidence: 99%